Integrated transcriptome analysis of CSE1L regarding poor prognosis and immune infiltration in bladder urothelial carcinoma and experimental verification - Liu, Runze; Ma, Jiayi; Zhang, Yong; Zhou, Zhongbao (Frontiers in Immunology, 2024)
Background: Bladder urothelial carcinoma (BLCA) is one of the most prevalent tumors globally, with its incidence rising notably in developed countries, significantly affecting human health. CSE1L encodes a protein that is involved in various cellular processes and plays a critical role in cancer initiation and progression. However, its role in BLCA remains underexplored. Methods: CSE1L expression in BLCA was analyzed using TCGA data and validated by qRT-PCR and Western blot in clinical samples. Survival analysis and Cox regression models were used to evaluate its prognostic value. Functional enrichment and protein interaction analyses were performed, and immune cell infiltration was assessed using CIBERSORT. Drug sensitivity was analyzed using GDSC data. In vitro assays evaluated the effects of CSE1L knockdown on cell proliferation, migration, and invasion. Results: CSE1L was found to be significantly overexpressed in BLCA tissues compared to normal tissues. High CSE1L expression was associated with poor overall survival and unfavorable clinicopathological features. Functional enrichment analysis revealed that DEGs related to CSE1L were involved in cell cycle regulation and immune-related pathways. Immune infiltration analysis indicated a significant correlation between CSE1L expression and various immune cell types, particularly T cells and macrophages. Drug sensitivity analysis identified several chemotherapeutic agents, including MG-132, Palbociclib, and Nutlin-3a, which were more effective in the low-CSE1L expression group, while the high-CSE1L expression group showed sensitivity to drugs like S-Trityl-L-cysteine, Bleomycin, and Cisplatin. In vitro knockdown of CSE1L in BLCA cell lines inhibited cell proliferation, migration, and invasion. Conclusions: The overexpression of CSE1L is associated with the progression and poor prognosis of bladder cancer, suggesting it could be a promising target for bladder cancer in the future.